2021
DOI: 10.1371/journal.pone.0244696
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Childhood Experiences are associated with choice of partner, both partners' relationship and psychosocial health as reported one year after birth of a common child. A cross-sectional study

Abstract: Adverse Childhood Experiences (ACEs) are common and known to have consequences for individuals’ adult health, leading to a higher risk of illness. The aims of the study were to investigate the ACEs in couples, to examine the extent of assortative mating and to investigate the association between the relationship of the load of ACEs within couples and health outcomes, one year after the birth of a common child. At antenatal clinics in Sweden 818 couples were recruited and investigated one year after the birth o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 39 publications
2
10
0
1
Order By: Relevance
“…Furthermore, results showed that the ACEs of one parent were correlated with the caregiving provided by a second parent. Assortative mating processes also may contribute to the non-random selection of romantic partners who share similar backgrounds and characteristics (Andersen, 2018; Andersson et al, 2021; Font et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, results showed that the ACEs of one parent were correlated with the caregiving provided by a second parent. Assortative mating processes also may contribute to the non-random selection of romantic partners who share similar backgrounds and characteristics (Andersen, 2018; Andersson et al, 2021; Font et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, since the late 1950s, the literature on fathers’ depressive reactions during their wives’ pregnancies has not kept pace with that on women’s perinatal depression (1733 records on PubMed on 13 August 2022 vs. 11,602 results on the same database on the same day). This disparity is regretted by investigators of fathers’ perinatal depression, because its consequence is that fewer resources are available for dedicated programs directed to counteracting paternal depression [ 7 , 8 ]. The fact that there are no diagnostic criteria for paternal depression in commonly accepted diagnostic systems [ 9 ] renders this disparity a natural consequence.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study also found that women who experienced ACEs tended to have husbands with ACEs as well 48 . Moreover, ACEs themselves can increase the risks of lower socioeconomic status, substance abuse, and cardiovascular risks, then those consequences may further influence mate choice in different ways 8,49 .…”
Section: Discussionmentioning
confidence: 90%
“…Spousal concordance in ACEs can be explained by the assortative mating theory, which proposes that people are inclined to marry partners who are similar to them in some way, such as socioeconomic status, lifestyle, and even cardiovascular risk 13,46,47 . A recent study also found that women who experienced ACEs tended to have husbands with ACEs as well 48 . Moreover, ACEs themselves can increase the risks of lower socioeconomic status, substance abuse, and cardiovascular risks, then those consequences may further influence mate choice in different ways 8,49 .…”
Section: Discussionmentioning
confidence: 90%